Practical rails projects - Alameda, Eldon; SpringerLink (Online service) (Berkeley, CA : Springer, 2007)
Provides instructions for creating Rails applications, describing such features as cashing options, connecting to a legacy database, building generators, and building an XML-RPC API.
Includes index.
Keywords: Ruby on rails (Electronic resource); Web site development; Ruby (Computer program language); Online social networks; Application software -- Design